2018
DOI: 10.1016/j.aquatox.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics cause neurotoxicity, oxidative damage and energy-related changes and interact with the bioaccumulation of mercury in the European seabass, Dicentrarchus labrax (Linnaeus, 1758)

Abstract: Microplastics pollution is a global paradigm that raises concern in relation to environmental and human health. This study investigated toxic effects of microplastics and mercury in the European seabass (Dicentrarchus labrax), a marine fish widely used as food for humans. A short-term (96 h) laboratory bioassay was done by exposing juvenile fish to microplastics (0.26 and 0.69 mg/L), mercury (0.010 and 0.016 mg/L) and binary mixtures of the two substances using the same concentrations, through test media. Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
181
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 541 publications
(216 citation statements)
references
References 68 publications
15
181
1
1
Order By: Relevance
“…In line with MPs/NPs activity as carriers or vectors of environmental contaminants, studies using fish cell lines have revealed that, while pristine plastics show no toxicity, those sampled from different islands around the world do [96], and so do those that have been mixed with human pharmaceuticals [97]. MPs/NPs were shown to modulate the toxicities a range of pollutants/toxicants, including phenanthrene [75], mercury [49], cadmium [46][47][48], polychlorinated biphenyls (PCBs) [98], gold ions [99], and the antibiotic roxithromycin [100], in fishes. However, adsorption of toxicants by the plastics could also potentially lower their toxicity, and such is the case for a complex mixture of polycyclic aromatic hydrocarbons (PAHs) [101].…”
Section: Toxicity Of Mps/nps In Fishesmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with MPs/NPs activity as carriers or vectors of environmental contaminants, studies using fish cell lines have revealed that, while pristine plastics show no toxicity, those sampled from different islands around the world do [96], and so do those that have been mixed with human pharmaceuticals [97]. MPs/NPs were shown to modulate the toxicities a range of pollutants/toxicants, including phenanthrene [75], mercury [49], cadmium [46][47][48], polychlorinated biphenyls (PCBs) [98], gold ions [99], and the antibiotic roxithromycin [100], in fishes. However, adsorption of toxicants by the plastics could also potentially lower their toxicity, and such is the case for a complex mixture of polycyclic aromatic hydrocarbons (PAHs) [101].…”
Section: Toxicity Of Mps/nps In Fishesmentioning
confidence: 99%
“…For the gut, pathological manifestations of MP/NP toxicity include documented changes in gut biomarkers related to epithelial barrier integrity, inflammation, and oxidative stress [83,86], as well as changes in gut microbiota [82,83,86]. In the case of liver, changes in metabolites, key metabolic enzymes, and oxidative stress-induced enzymes occur [49,74,79,81,85,87]. MPs/NPs could be internalized [88], and then cause detectable biomarker changes in blood cells [47,88,89].…”
Section: Toxicity Of Mps/nps In Fishesmentioning
confidence: 99%
See 2 more Smart Citations
“…They then fed these nauplii to zebrafish ( Danio rerio ) and observed trophic transfer of both the microplastics and benzo(a)pyrene. Most such studies examined organic pollutants, but Barboza et al () evaluated interactions between mercury and microplastics, and resulting toxicological implications in fish.…”
Section: Microplastic Uptake and Consequences In Biotamentioning
confidence: 99%